Growth of 3C–SiC films on Si substrates by vapor–liquid–solid tri-phase epitaxy. Issue 6 (July 2015) - Liang, Yu-Ling; Lu, Shih-Zong; Lee, Hsin-Ying; Qi, Xiaoding; Huang, Jow-Lay
Abstract: Cubic SiC films (3C–SiC) were deposited on (111) Si substrates by a vapor–liquid–solid tri-phase growth method. In such a process a thin copper layer, which was evaporated on the Si substrate prior to the growth, was melted at high temperature as the flux and then methane (carbon source) was diffused into the liquid layer to react with Si, leading to the growth of SiC on the substrate. Copper showed some good properties as the flux, including high silicon and carbon solubility, low growth temperature and low volatility. Suitable growth parameters to go with the copper flux were identified, under which (111) textured 3C–SiC films were grown. Small numbers of (220) grains were observed to embed in the (111) films, which were difficult to avoid completely. Etching pits of the Cu melt on the substrate surface may act as the preferred sites for the growth of (220) grains.